POTENSI IKAN KARANG DI PERAIRAN PESISIR NEGERI HUKURILA, KECAMATAN LEITIMUR SELATAN KOTA AMBON - Sahetapy, Dicky; Selanno, Debby; Tuhumury, Novianty (TRITON: Jurnal Manajemen Sumberdaya Perairan, 2019)
The Study was conducted on April to May 2019 in the coastal waters of Hukurila village, Leitimur Selatan District of Ambon city with the aims to analyzed taxon composition, species diversity, density, standing stock, potency of target species and status of reef fish. Reef fish data were collected at four reef stations using UVC method. The result showed that there were 192 species of reef fish inhabit coral reef of Hukurila village. Pomacentridae, Labridae and Chaetodontidae have high species richness, while other seven families have low species richness. Relative diversity of reef fish in the study area can be classified in poor to moderate category, and the estimated number of species of reef fish was 369 species. Species diversity of reef fish is high, with low species dominance in the community and species evenness of reef fish in their community is in stable condition. Density of reef fish between reef station ranged of 2.9-4.0 ind. m-2. Furthermore, the standing stock of reef fish ranged of 28,840-40,400 ind.ha-1 and biomass of target reef fish species ranged of 1.67-5.14 (Â± 3.53) tons ha-1 of coral reefs. Status of reef fish in the coral reef of Hukurila village belong to high category. ABSTRAK Penelitian dilakukan dari April sampai Mei 2019 di perairan pesisir Negeri Hukurila, Kecamatan Leitimur Selatan Kota Ambon dengan tujuan menganalisis komposisi taksa, diversitas spesies, densitas, sediaan cadang, potensi ikan karang spesies target dan status ikan karang. Data ikan karang dikumpulkan dari 4 stasiun dengan metode underwater visual census (UVC). Ditemukan 192 spesies ikan karang Menempati terumbu karang Hukurila. Famili Pomacentridae, Labridae, Chaetodontidae memiliki kekayaan spesies tinggi, sementara tujuh famili memiliki kekayaan spesies rendah. Diversitas relatif ikan karang di areal studi termasuk kategori miskin hingga moderat, dan diestimasi jumlah spesies ikan karang pada habitat terumbu Negeri Hukurila sebanyak 369 spesies. Diversitas spesies ikan karang tinggi, dengan dominansi spesies rendah dalam komunitas dan keserasian spesies ikan karang dalam kondisi Stabil. Densitas ikan karang antara stasiun terumbu berkisar antara 2.9 - 4.0 ind/m2. Sediaan cadang ikan karang antara stasiun terumbu berkisar antara 28.840 - 40.400 ind/ha dan potensi spesies target berkisar 1,67-5,14 (Â± 3,53) ton/ha terumbu karang. Kondisi ikan karang di terumbu Negeri Hukurila termasuk kategori tinggi. Kata kunci: Ikan karang, keanekaragaman spesies, kepadatan, sediaan cadang, potensi